Fuzzy Information and Z-number-based Approaches to Energy Resource Selection - Nuriyev, Mahammad (International Journal of Energy Economics and Policy, 2020)
In this paper, we study models for ranking renewables and a mix of energy resources in the development of long-term energy policy. Energy resource selection is a multi-criteria decision-making problem, characterized by incomplete information, uncertainties and intangibles, competitive priorities and contradictory requirements. The uniqueness of the problem and the limited relevant data necessitates the use of expert opinion as a principal source of information. All these factors contribute to subjectivity and vagueness in the decision-making process. Taking into consideration these circumstances, fuzzy information and a Z-number-based Analytic Hierarchy Process (AHP) has been used as a decision-making tool. Z–number represents both the restriction and the reliability of evaluation and, due to these characteristics, it provides a better description of the uncertainty. Numerical examples and comparative analysis of fuzzy and Z-number-based models illustrate the process to solution and results. Keywords: energy resources, fuzzy information, AHP, Z-number, multi-criteria decision. JEL Classifications: Q42, Q48, Q35 DOI: https://doi.org/10.32479/ijeep.9250